Discursive Strategies of Verbal Violence in the Users Comments on Facebook News Updates - Muwafiq, Ahmad Zulfahmi; Sumarlam, Sumarlam; Kristina, Diah (Jurnal Ilmiah Peuradeun, 2019)
This article explores how verbal violence on Facebook was performed by the users. It investigates the discursive strategy exploited by them. The data of verbal violence were taken from user comments to news update posted on Indonesian news portal fans pages under the topic of Paris tragedy. The comments were taken from four different Indonesian news fans pages, namely Detik.com, Kompas.com, Liputan6.com and Tribunnews.com. The collected data were analyzed qualitatively. Applying Discourse Historical Approach (DHA) proposed by Wodak, the result shows that the users exploits three strategies to perform verbal violence namely referential strategy, predicative strategy and argumentation strategy. Employing referential strategy, verbal violence is realized in the form of noun and noun phrase, which functions as subject, object and modifier of noun phrase. Employing predicative strategy, verbal violence is realized in the form of word, phrase and clause, which function as attribute or predicate. Employing argumentation strategy, verbal violence is realized in the form of sentence and discourse.